SISTEM KUNCI ELEKTRONIS DENGAN PEREKAM WAKTU AKSES BERBASIS MIKROKONTROLER AT89C51 - -, Subandi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
The technology development nowadays, especially electronic technology has been reaching great strides. Every technology in almost any sector needs electronic device. As a door lock, now, can used electronic technology as its controller system. To make electronic key system has few steps. First, make planning to design electronic and mechanic system of the door lock. Second, design the hardware and drill PCB followed by assembly the electronic component. Third, design software by using algorithm from system. Fourth, flash the assembler program into the IC AT89C51 and set it to hardware, next test the completed system. Microcontroller system on that application connected to another interface like as ADC, DAC, LCD etc. The finishing from the system is checked. The result, this system can be applied to door lock system with time recording access. It uses Real Time Clock (RTC), Line Port Terminal (LPT), IC AT89C51 and hand phone Siemens M35i as the interface system.